PENEGAKAN HUKUM PEMERINTAHAN BERDASARKAN SURAT EDARAN WALIKOTA NOMOR 1 TAHUN 2018 TENTANG AKSI BERSIH KOTA PEKANBARU TAHUN 2018-2019 - Saraswati, Fiandar Gita; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Writing a thesis entitled "Government Law Enforcement based on Mayor Circular Letter Number 1 of 2018 concerning Clean Action for Pekanbaru City 2018-2019" Law enforcement is a process to make legal wishes come true. Government law enforcement is not only shown to give punishment to citizens who violate the rules of a circular letter. however, it also aims to prevent actions and actions that may cause discomfort and cleanliness to the city of Pekanbaru. The inhibiting factors in law enforcement are internal and external factors. This research was conducted at the Department of Environment and Sanitation, Pekanbaru City. The purpose of this paper is to determine the enforcement of government law by the Department of Environment and Sanitation of Pekanbaru City in its implementation in the field in 2018-2019. The theory used is the theory of discretion. The research method used is descriptive qualitative with interview and documentation data collection techniques, the type of data used is secondary data and primary data. The final conclusion of this research is to use discretionary theory in which the Mayor has the right to make regulations according to his own opinion in the presence of community developments which have an impact on the occurrence of certain circumstances that are urgent to play a maximum role in serving the interests of the community and still refer to local regulations and laws. applicable. From the circular issued by the mayor, the law enforcement has not been fully implemented properly.Â Keywords: Government Law Enforcement, Discretion and Circular of the Mayor of PekanbaruÂ